Perbedaan Kemampuan Komunikasi Matematik Siswa Antara Yang Mendapatkan Model Pembelajaran Student Teams Achievement Divisions Dengan Model Pembelajaranguided Note Taking: Studi Penelitian Kuasi Eksperimen di SMP Negeri 4 Garut - STKIP Garut Tahun 2012/2013) - Sartika, Gesti Pratiwi; Puspitasari, Nitta (Department of Mathematics Education Program IPI Garut, 2013)
Experiment with pra-experiment (the statistic group pretest-posttest design) aimed to find out the difference's ability of mathematic communication student between the students who got “Student Teams Achievement Division” learning model with “Guided Note Taking” learning model. Furthermore, the researcher discovered the attitude of student toward learning mathematics using “Student Teams Achievement Divisions” learning model with “Guided Note Taking” learning model. The result showed that:(1) There is no differences between the communication skills of students' mathematic which gain “Student Teams Achievement Divisions